1993
DOI: 10.1093/tropej/39.3.142
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Hospital and Clinic-based Breastfeeding Promotion Programme in a Middle Class Urban Environment

Abstract: Hospital interventions in support of breastfeeding have been highly successful in areas where the indigenous population has a well established environment of breastfeeding. However, programmes designed to improve breastfeeding patterns in urban populations have met with mixed success. This paper presents a prospective intervention study with a control group in which a health system-based breastfeeding promotion programme was initiated to support optimal breastfeeding for both child health and child spacing. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
12

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 0 publications
3
39
1
12
Order By: Relevance
“…Vários estudos demonstraram que é possível melhorar as práticas que estimulam o aleitamento materno nas maternidades com o treinamento de 18 horas da IHAC, tendo como base o cumprimento dos 10 passos para o sucesso do aleitamento materno [8][9][10][11][12][13][14] .…”
Section: Introductionunclassified
“…Vários estudos demonstraram que é possível melhorar as práticas que estimulam o aleitamento materno nas maternidades com o treinamento de 18 horas da IHAC, tendo como base o cumprimento dos 10 passos para o sucesso do aleitamento materno [8][9][10][11][12][13][14] .…”
Section: Introductionunclassified
“…Según informes procedentes de hospitales en la India y Pakistán (16,17), a la mayoría de las madres que fueron remitidas a clínicas para el manejo de la lactancia se les pudo ayudar a superar las dificultades propias del amamantamiento y a continuar la lactancia materna exclusiva. En otros países, los servicios de apoyo y orientación también han contribuido a aumentar la frecuencia de la lactancia materna exclusiva (18). Nuestro estudio difiere de los antedichos porque los niños no habían nacido en el hospital ni fueron remitidos a otros servicios para el manejo de la lactancia materna.…”
Section: Discussionunclassified
“…In a study conducted to reveal the variables associated with stunted growth in school children, Amigo et al 50 showed that environmental factors, such as paternal alcoholism, lack of good health care, poor hygiene, malnutrition, and a short breastfeeding period, were factors contributing to stunted growth. This led to the introduction of programs to promote breastfeeding 31,53,54 , which seem to have had positive effects, particularly in rural areas 55 . Adolescent mothers were found to be most likely to discontinue breastfeeding early 56 .…”
Section: Childcare In the Nineteenth Century: Foundling Homesmentioning
confidence: 99%